Surgical Risks and Advance Directives - Lederer, Daniel H. (The Hastings Center report, 1987)
Mrs. P is a seventy-six-year old woman with osteoporosis and a failed left hip prosthesis. In addition, she has severe chronic asthmatic bronchitis. The management of her lung disease has been hampered by her allergy to theophylline, which is one of the mainstays of treatment. As a result, she has had increasing difficulty walking and confinement to a wheelchair is imminent. When surgery to replace the prosthesis was recommended, Mrs. P expressed concern about the possibility of ending up after the operation dependent on a ventilator, possibly comatose. She feared that her resources would be depleted for medical expenses. Little or nothing would be left to pass on to her children. She was willing to have an operation only if she could prepare a legal document that, in the event of prolonged ventilator dependence, would require her physician to remove her from the ventilator after a specified time (for example, two weeks). Should the surgeon agree to be bound by Mrs. P's instructions, or should he refuse her request even if doing so means that she will not have the surgery that might prevent increasing disability?